Oylama Gücünün Enflasyon Üzerindeki Etkisi - Haydaroğlu, Ceyhun (Muş Alparslan Üniversitesi, 2020)
The relation between economy and politics shows itself in its sharpest way in the economy politics of the governments. The aim of this study is to add one more variable to the variables found in political instability literature and put forward its relation with inflation. Voting power expresses the power of opposition parties and ruling party in any decision making process. Another aim of the study is to analyse the effects of voting power on inflation which are mostly used in instability literature and Normalized Banzhaf Index value which is formed regarding to the election results of 47 countries in the 1987-2019 period. According to the analysis results, total power index values of the coalition parties and the governing party are inversely proportional with inflation and significant results are obtained for all the variables. The power voting index of the main opposition parties and inflation has a directly proportional effect and meaningful relation.

Ekonomi ve politika arasındaki ilişki kendisini en net şekilde hükümetlerin ekonomi politikalarında gösterir. Çalışmanın amacı politik istikrarsızlık literatüründe yer alan ampirik araştırmalardaki değişkenlere yeni bir değişken ekleyerek, enflasyon ile oylama gücü arasındaki ilişkiyi ortaya koymaktır. Oy gücü, siyasal karar alma mekanizmasında iktidardaki veya muhalefetteki partilerin bir karar almada ellerinde bulundurdukları güçtür. Çalışmada oylama gücünün 47 ülkenin 1987-2019 döneminde gerçekleşen seçim sonuçları temelinde oluşturulan ve çoğunlukla istikrarsızlık literatüründe kullanılan Normalize Edilmiş Banzhaf İndeksi değerleri ile enflasyon üzerindeki etkisi analiz edilmektedir. Analiz sonuçlarına göre, İktidarı oluşturan büyük partinin ve koalisyonu sağlayan partilerin güç indeks değerleri istatistiksel olarak enflasyon üzerinde anlamlı negatif etkiye sahiptir. Ana muhalefet partilerinin oylama gü
The Effect of Voting Power on Inflation
anemon
Keywords: Voting Power; Normalized Banzhaf Index; Inflation; Oy Gücü; Banzhaf Güç İndeksi; Enflasyon